Comparison of top-performing search strategies for detecting clinically sound treatment studies and systematic reviews in MEDLINE and EMBASE - WONG, Sharon S.-L; WILCZYNSKI, Nancy L; HAYNES, R. Brian (Journal of the Medical Library Association, 2006)
EMBASE searching is not free but has greater coverage of European and non-English language publications and topics such as pharmaceuticals, psychiatry, toxicology, and alternative medicine. Search strategies were treated as "diagnostic tests" for sound studies, and the manual review (hand search) was treated as the "gold standard." Considering the unique content coverage and search terms available in MEDLINE and EMBASE, information professionals would be best served by searching the database that is most relevant to their setting or searching both databases to improve a comprehensive search.